Vulnerability assessment of touristic village in Nepal Himalayas: A case study of Lwang village - Kafle, Pradeep; Upadhyay, Magnus; Shreedhar Khakurel, (Journal of Engineering Issues and Solutions, 2024)
Nepal is located in a seismically active zone and masonry structures are widely constructed throughout the country. Lwang Village a popular tourist destination in Western Nepal contains several masonry houses. This study aims to assess the vulnerability of these buildings using the vulnerability index (Iv) method. Data from 24 houses were analysed resulting in a mean Iv of 71.3. A vulnerability curve was subsequently plotted to evaluate the potential damage under earthquake scenarios similar to the Jajarkot and Gorkha earthquakes. The analysis indicated that during an earthquake of intensity comparable to the Jajarkot event, a significant portion of buildings would experience moderate to heavy damage. In addition, an earthquake similar to the Gorkha event would result in very heavy damage to near collapse for many structures. Specifically, 45.83% of the buildings are expected to suffer heavy damage, and 50% could near collapse during an Intensity X event. These findings highlight the urgent need for targeted strengthening measures to enhance the seismic resilience of buildings in Lwang Village, thereby safeguarding both the local community and the area's touristic value.